Bridging Teaching Experience and Reflective Academic Writing through Photovoice: Indonesian PLP–KKN Students in Thailand - Adawiyah, Dita; Sulistiyo, Urip (Indonesian Research Journal in Education |IRJE|, 2026)
This study aimed to explore how Photovoice supported Indonesian pre-service teachers participating in an international Praktik Lapangan Persekolahan and Community Service program (PLP–KKN) in Thailand in developing reflective academic writing based on their teaching experiences. The study focused exclusively on the Indonesian PLP–KKN students, while the teaching context in Thailand functioned as an intercultural learning environment rather than the object of investigation. A qualitative case study design was employed, involving two Indonesian student-teachers. Data were collected through Photovoice-based reflective writing and follow-up interviews. In this study, photographs functioned as reflective prompts that helped participants recall experiences, reflect on meaningful teaching moments, and organize their ideas in writing. The findings revealed that Photovoice helped participants express their teaching experiences more clearly and meaningfully in reflective academic writing. The use of photographs encouraged deeper reflection, supported idea development, and helped connect personal experiences with academic reflection. This study concludes that Photovoice can serve as a practical and effective reflective tool in international practicum and service-learning programs, particularly in supporting pre-service teachers’ reflective thinking and reflective academic writing in intercultural learning contexts.